Dynamic modeling and displacement control for differential flatness of quadrotor UAV slung-load system - Roy, Kumud Ranjan; Waghmare, Laxman M.; Patre, Balasaheb M. (International journal of dynamics and control, 2023)
In this paper, the quantitative simulation studies of a quadrotor unmanned aerial vehicles (Q-UAVs) carrying a payload are designed and holding a robust position and attitude tracking control problem of a Q-UAVs subject to system nonlinearities, input coupling, aerodynamic uncertainties and external wind disturbances are investigated. The flight dynamics of the Q-UAVs are changed once the load is slung beneath them via cable, causing the UAVs’ stability to be disrupted. The oscillation could become unstable, limiting the performance of UAVs and interfering with the proper positioning of the load. In contrast to the external disturbance, the contrary results are related to the properties of the quadrotor UAV (Q-UAV) and the payload. In terms of making UAVs capable of adapting to changes in dynamical systems and reducing the effects generated by load swing, one model-based approach is addressed for Q-UAV with a single slung payload. The slung payload’s mass point is modeled and simulated as a pendulum, and all disturbances are taken into account and investigated. For the purposes, a disturbance observer-based robustify input–output linearization control scheme is proposed, referred to as nonlinear dynamic inversion. The proposed methodology and the model developed can estimate the lumped disturbance, thereby enabling the rejection of the same, operating on the Q-UAV, and assisting in expecting the trajectory motion at the desired value of displacement of quadrotor UAV slung-load system, allowing for improved load placement accuracy.